The Influence of Compensation and Work Motivation on Employee Productivity at The Naura Seafood Frozen Sidoarjo Store - Elsa Putri Hartanti (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
To increase profits for the company, a highly motivated workforce is needed. Profits will increase if supported by good worker productivity. Achieving these goals depends on the policies taken by the company. However, on the other hand, workers' work productivity decreases due to low work motivation and compensation that is relatively only sufficient for workers' basic living needs; this results in targeted production not being achieved according to the targets set. Company, regarding goals. This research aims to determine (1) the compensation provided by the Naura Frozen Seafood Shop in Sidoarjo, (2) the work motivation of workers at the Naura Frozen Seafood Shop in Sidoarjo, (3) work productivity at the Naura Frozen Seafood Shop in Sidoarjo, and (4) the influence of compensation and motivation both collectively and individually on work productivity at the Naura frozen seafood shop in Sidoarjo. The method used is descriptive and an expansive survey of the Naura Seafood Frozen Sidoarjo shop workers analysis unit. Sampling used a simple random sampling method with a sample size (n) of 85 workers. The type of research in this research is causality, the time horizon in this research is cross-sectional, and the analysis methods used are frequency distribution and path analysis. The findings of this research are that compensation and motivation both jointly and individually influence the work productivity of workers at the Naura Seafood Frozen Sidoarjo shop. However, partial motivation is more dominant in influencing work productivity than compensation.